2016
DOI: 10.1177/2331216516670279
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Compensation of Speech Perception With Hearing Impairment, Cochlear Implants, and Aging

Abstract: External degradations in incoming speech reduce understanding, and hearing impairment further compounds the problem. While cognitive mechanisms alleviate some of the difficulties, their effectiveness may change with age. In our research, reviewed here, we investigated cognitive compensation with hearing impairment, cochlear implants, and aging, via (a) phonemic restoration as a measure of top-down filling of missing speech, (b) listening effort and response times as a measure of increased cognitive processing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 136 publications
(182 reference statements)
1
47
0
Order By: Relevance
“…Although consistent with our predictions, the magnitude of the effect of MTB on speech recognition is notable. For all participants, but especially the CI-4 listeners, accuracy scores were near floor at þ10 dB SNR, suggesting that, in addition to the MTB, the task and materials might be quite challenging for CI users, perhaps due to the interleaved speaking style and talker variability and lack of strong semantic information with which listeners might compensate for the degraded conditions (Başkent et al, 2016a(Başkent et al, , 2016b; see Tamati et al, 2019 for additional information about the materials). Across listeners, as expected, the CI-8 listeners were found to have the best performance across all tasks, while the CI-4 listeners had the poorest performance, and CI users were spread relatively evenly across the range of scores, confirming our design choice for approximating good and poor CI listening with 8-and 4-channel noise-vocoder simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although consistent with our predictions, the magnitude of the effect of MTB on speech recognition is notable. For all participants, but especially the CI-4 listeners, accuracy scores were near floor at þ10 dB SNR, suggesting that, in addition to the MTB, the task and materials might be quite challenging for CI users, perhaps due to the interleaved speaking style and talker variability and lack of strong semantic information with which listeners might compensate for the degraded conditions (Başkent et al, 2016a(Başkent et al, , 2016b; see Tamati et al, 2019 for additional information about the materials). Across listeners, as expected, the CI-8 listeners were found to have the best performance across all tasks, while the CI-4 listeners had the poorest performance, and CI users were spread relatively evenly across the range of scores, confirming our design choice for approximating good and poor CI listening with 8-and 4-channel noise-vocoder simulations.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that predictive relations of cognitive and linguistic variables with spoken word recognition might exist only in groups of listeners that are homogeneous with respect to other variables that affect implant use. In addition, Baskent et al. (2016) concluded that the interaction between bottom-up information in case of degraded speech and how this degradation can be compensated for using cognitive mechanisms is complex.…”
Section: Discussionmentioning
confidence: 99%
“… Warren and Sherman (1974) showed that later-occurring semantic context can play an influential role in restoring missing sounds even when local acoustic cues to missing words (like coarticulation) are neutralized. It would be ideal for a listener to use context predictively, to aid in the recognition of upcoming words ( Altmann & Kamide, 1999 ; 2007 ; Tavano & Scharinger, 2015 ), but such a process might not be recoverable from behavioral measures ( Başkent et al., 2016 ), since a word could have been perceived correctly or restored with the aid of contextual cues, but result in a correct score either way ( Samuel, 1981 ).…”
Section: Introductionmentioning
confidence: 99%